Examining the Learning Styles and Academic Success Motivations of Prospective Students Who will Take a Physical Education Special Skill Exam Based on a Few Parameters - Abdullah Sencer Temel; Mevlüt Aydoğmuş; Yalçın Tükel; Davut Atılgan (Physical Education of Students)
Background and Study Aim: Learning styles are the foundation of how students learn and the unique paths to individual development; so they must be considered when assessing academic progress. The primary objective of this research endeavor is to investigate the learning styles and academic motivation exhibited by individuals aspiring to enroll in the faculty of sports sciences. In pursuit of this aim, a comparative methodology was employed, enabling a comprehensive analysis of various variables, including gender, sports branch, and school achievement scores. Material and Methods:The study's population comprises 4,104 candidates who applied to the special talent entrance examination at the Faculty of Sport Sciences in the Selcuk University. A survey was administered to a sample of 378 individuals, consisting of 215 male and 163 female students, who are planning to take the special skill entrance exam for the faculty of sport science. Selcuk University and Necmettin Erbakan University, both located in Konya, employed a random sampling methodology to select prospective students for participation in the study. The questionnaire served as the primary instrument for conducting descriptive, correlational, and regression analyses. To fulfill the research objectives, the Academic Motivation Scale and Kolb Learning Styles Inventory were employed. The reliability and validity of these scales were rigorously examined by the researchers. This study clarified the impact of prospective students' learning styles and academic motivations on their future learning experiences and performances in the faculty of sports sciences. Results: The study revealed that individuals who used converging, accommodating, and multiple learning styles demonstrated significantly higher levels of academic motivation. Conclusions: Further, this paper provides evidence that students who utilized multiple learning styles had significantly higher academic motivation.